INTEGRATING REVELATION AND REASON IN THE SCIENTIFIC FRAMEWORK OF ISLAMIC HIGHER EDUCATION: THE WAHDATUL ULUM PARADIGM - Sirait, Nilna Mayang Kencana; Sukiman, Sukiman; Al-Farabi, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Islamic higher education in Indonesia has undergone significant changes in the last two decades. The institutional shift from IAIN to UIN has brought epistemological challenges in integrating religious and rational sciences. The Wahdatul 'Ulum paradigm developed at UIN North Sumatra aims to resolve scientific dualism by using a scientific framework based on tauhid. Purpose: Wahdatul 'Ulum is an epistemological paradigm that integrates Islamic knowledge and rational knowledge within a consistent and transformative framework. Method: This study uses a qualitative case study with data collection techniques through in-depth interviews, analysis of institutional documents, and participatory observation at UINSU. Results: Findings show that the Wahdatul 'Ulum paradigm is built on three main foundations: ontological, namely tauhid as the essence of all knowledge; epistemological, namely the integration of revelation and reason; and axiological, namely a focus on social transformation through education. Conclusion: The Wahdatul 'Ulum paradigm transcends theological debates and functions as an integrative scientific model that reinterprets the purpose of Islamic higher education and contributes to the global discourse on the decolonization of knowledge.